Dendritic rhodium catalyst precursors for the hydroformylation of olefins - Williams, Cody (Department of Chemistry, 2019)
The hydroformylation reaction is the transition-metal catalysed addition of CO/H2 to olefins, resulting in linear and/or branched aldehydes. This reaction is in accordance with Green Chemistry principles, as it operates with 100% atom efficiency and uses renewable feedstocks such as olefins from the Fischer-Tropsch process. Rhodium is the metal of choice when designing catalysts for hydroformylation, owing to its good catalytic activity under mild reaction conditions. The strategy of appending bulky ligands has often been employed to enhance catalytic activity and selectivity. Dendritic wedges are promising to the field of catalysis, as one branch may possess multiple surface terminal groups and the other branch may consist of a mononuclear metal centre. This method differs to classical approaches whereby multinuclear effects are explored to enhance the catalyst activity. The purpose of this study was to synthesize and characterise a series of Fréchet dendrons bearing rhodium Schiff-base moieties at the focal point, and investigate their potential as catalyst precursors in the hydroformylation of olefins. A series of Fréchet dendrons with methyl ester groups at the periphery were prepared. The N,O-salicylaldimine and N,P-iminophosphine Schiff-base ligands were synthesized and consequently coupled to the Fréchet dendrons to yield a new class of Fréchet dendrons with N,O-salicylaldimine or N,P-iminophosphine ligands at the focal point. Complexes of these ligands were synthesized to form a new series of neutral rhodium(I) metallodendrons. Complexation of the N,O-salicylaldimine Fréchet dendrons with the metal-precursor [Rh(μ-Cl)(η 2 :η2 -COD)]2 (where COD = 1,5-cyclooctadiene) afforded the Rh(I)-COD metallodendrons. The Rh(I)-COD metallodendrons were reacted under a carbon monoxide atmosphere to yield a new series of dicarbonyl Rh(I) metallodendrons. The bridge splitting reaction between the N,P-iminophosphine Fréchet dendrons and [Rh(μ-Cl)(CO)2]2 afforded the carbonyl-chloride Rh(I) metallodendrons. The Fréchet dendron ligands and rhodium metallodendrons were fully characterised using an array of spectroscopic (1H, 13C{1H}, 31P{1H} NMR, FT-IR spectroscopy) and analytical (elemental analysis and mass spectrometry) techniques. Single crystal X-ray diffraction confirmed the proposed molecular structure and square-planar geometry around the metal centre for the zeroth generation analogues of the N,O-salicylaldimine and N,P-iminophosphine rhodium metallodendrons. The Rh(I) Schiff-base metallodendrons were applied as catalyst precursors in the hydroformylation of various olefins. All of the catalyst precursors were active in the hydroformylation of 1-octene. The N,O-salicylaldimine metallodendrons displayed good to excellent conversion (78 – 100%), good chemoselectivity (66 – 95%) and moderate regioselectivity (51 – 67%). In contrast, the N,P-iminophosphine metallodendrons displayed low conversion (4 – 8%), good chemoselectivity (76 – 80%) and good regioselectivity (64 – 68%) under the hydroformylation conditions. Notably, the increase in dendron size (G0 – G2) resulted in an increase in the chemoselectivity towards aldehydes. Hydroformylation reactions were conducted using various olefin substrates. These include 1-octene, styrene, 7-tetradecene, methyl oleate, triolein, D-limonene and R-citronellal. The model precursor was active in the hydroformylation of these substrates. More importantly, conversions obtained were promising for styrene (100%), D-limonene (90%), 1-octene (86%), methyl oleate (78%), 7-tetradecene (73%) and triolein (52%). The regioselectivity for the internal olefins ranged between 85 – 98%. These results are particularly promising for tandem-catalytic processes. Mercury drop experiments performed on the zeroth generation analogues of the N,O-salicylaldimine-COD, N,O-salicylaldimine-dicarbonyl and N,P-iminophosphine chloro-carbonyl rhodium(I) metallodendrons displayed suppressed activity in the presence of mercury.